The allocation of talent in teacher's occupation and Economic Growth - Moura, Paulo Vitor Antonacci (2018)
The quality of teachers is a determining factor in the formation of human cap-ital, so it is also an object of study of economic development. We develop a generalequilibrium model in which workers are heterogeneous and make decisions in a labormaket with frictions. Additionally, teacher quality is input to human capital formation.Empirically we use a cross country dataset to check the results. We also simulate theUS’s labour market frictions to all economies. We found that improving the eviromentwhere teacher’s occupational choices are made, we increase the overall productivity by 110%